2022
DOI: 10.3390/su14148455
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Modeling of Soil Organic Matter Based on Characteristic Wavelength in East China

Abstract: Soil organic matter (SOM) is a key index of soil fertility. Visible and near-infrared (VNIR, 350–2500 nm) reflectance spectroscopy is an effective method for modeling SOM content. Characteristic wavelength screening and spectral transformation may improve the performance of SOM prediction. This study aimed to explore the optimal combination of characteristic wavelength selection and spectral transformation for hyperspectral modeling of SOM. A total of 219 topsoil (0–20 cm) samples were collected from two soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…From the above results, some useful conclusions can be drawn: (1) for the same spectral transformation, RF models (for example, model CARS-R-RF) had lower accuracy, while the SVR and PLSR models (for example, model CARS-R-SVR and CARS-R-PLSR) have higher accuracy; (2) for the same modeling methods, SOM predicted models using R (model CARS-R-SVR) had lower accuracy, models using FDR and CR (model CARS-FDR-SVR and CARS-CR-SVR) had better accuracy. Overall, this study showed that CR and FDR transformation could improved modeling accuracy, and CARS algorithm could improve the SVR and PLSR modeling accuracy, that was consistent with most research results [ 13 , 17 , 18 , 34 ].…”
Section: Results Of Characteristic Band Screeningsupporting
confidence: 90%
See 4 more Smart Citations
“…From the above results, some useful conclusions can be drawn: (1) for the same spectral transformation, RF models (for example, model CARS-R-RF) had lower accuracy, while the SVR and PLSR models (for example, model CARS-R-SVR and CARS-R-PLSR) have higher accuracy; (2) for the same modeling methods, SOM predicted models using R (model CARS-R-SVR) had lower accuracy, models using FDR and CR (model CARS-FDR-SVR and CARS-CR-SVR) had better accuracy. Overall, this study showed that CR and FDR transformation could improved modeling accuracy, and CARS algorithm could improve the SVR and PLSR modeling accuracy, that was consistent with most research results [ 13 , 17 , 18 , 34 ].…”
Section: Results Of Characteristic Band Screeningsupporting
confidence: 90%
“…DOA was calculated using the reflectance of soil at 550, 600 and 650nm. SOM content was negatively correlated with DOA [ 24 , 27 , 45 ]. If the soil has rich SOM content, the reflectance spectral curve of soil shows a flat state in the range of 550–650 nm with low DOA value.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations